Uniform carbon coating drastically enhances the electrochemical performance of a Fe3O4 electrode for alkaline nickel–iron rechargeable batteries. (20th September 2019) - Tang, Hongwei; Sun, Zisheng; Chang, Kun; Hou, Yaolin; Li, Bao; Hou, Yan; Chang, Zhaorong
Abstract: Fe3 O4 @C composites for use in alkaline nickel-iron rechargeable batteries are synthesized via a spray drying method. SEM and TEM confirm that the Fe3 O4 @C composite is a secondary particle microsphere formed by many primary particles uniformly coated with carbon. The particles aggregate with each other, which is equivalent to forming a three-dimensional conductive mesh. The electrochemical properties of the bare Fe3 O4 and Fe3 O4 @C composites as anode materials for alkaline nickel-iron batteries are investigated. The results show that the Fe3 O4 @C composite synthesized by spray drying exhibits considerably high discharge capacities and an excellent rate capability. The specific discharge capacity of the Fe3 O4 @C composite reaches 693.7 mAh g −1 at a current density of 300 mA g −1, with a charging efficiency of 92.5%. Moreover, the Fe3 O4 @C composite exhibits an admirable cycling stability with a superior capacity retention of 92.0% for 100 cycles at a current density of 300 mA g −1 . In addition, discharge capacities of 556.7 and 420.1 mAh g −1 are achieved at high current densities of 1200 and 2400 mA g −1, respectively. Graphical abstract: Image 1 Highlights: Fe3 O4 @C composite is synthesized via a spray-drying method. Particles coated with carbon uniformly aggregate to form a three-dimensional conductive mesh. Fe3 O4 @C composite exhibits considerably high discharge capacities and an excellent rate capability.